Application of the LGE program to improve reading comprehension in second grade secondary school students of the educational institution “José Rosa Ara” of Tacna, 2016. - Mamani Flores, Dora Gladys (2020)
The strategic management of institutions of higher education presents a relatively low level of productivity; In this sense the fundamental question that has orientated the research in this field and that the researchers have tried to answer is: how do organizations reach and maintain their competitive advantage? This research seeks to demonstrate that strategic management is related to the increase of the student population, measured through the recruitment of students in the target market to which the university is directed. On the other hand, secondary information was used by the planning office of the Private University of Tacna. In addition, the Pearson correlation coefficient has been used to analyze the degree of strength and the meaning of the relevant variables of strategic management with the recruitment of students in order to verify the main hypothesis as well, the test of difference between two means was used to verify the specific hypotheses proposed.When contrasting the main hypothesis, it was found that the strategic management of the Private University of Tacna is directly and significantly related to the recruitment of students from its target. In the case of the specific hypotheses, there are no differences between planning and execution regarding the diffusion of intellectual production and the results of specialized training